REAL ASSESSMENT MODEL FOR MECHANICAL BEHAVIOR OF RECTANGULAR BEAMS ARCHITECTURE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Fiber Reinforced Polymer (FRP) as an outer support is utilized widely to manage the strengthnecessities connected with flexure and shear in underlying frameworks. Be that as it may, thefortifying of individuals exposed to twist is investigated as of late. Twist disappointment is anunfortunate fragile type of disappointment which ought to be kept away from extraordinarily inthe quake inclined regions. In the current work, the way of behaving and execution ofrectangular built up cement footers fortified with remotely reinforced Glass Fiber ReinforcedPolymer (GFRP) textures exposed to consolidated flexure and twist is concentrated tentatively.Rectangular RC radiates remotely fortified with GFRP textures were tried to disappointmentutilizing a game plan which move force to the focal piece of the pillar through two inversecantilevers called second arms. Each arm is exposed to rise to static stacking during theanalysis. Absolute nine RC radiates were projected and tried for the review.